Evolution of ergativity in the Western Hindi - Sigorskiy, Alexander A. (Lingua Posnaniensis, 2015)
The early stage of the Western Hindi vernaculars demonstrates two types of typology competing with each other - Nominative typology and Split Ergative typology. Ergative typology includes a number of ergative strategies existing in different vernaculars and in the one and the same vernacular as well. In the course of standardization of Modern Standard Hindi (MSH) Split Ergative Typology wins. The main features of Old Hindi case system are: 1) Old Hindi demonstrates the same, dative case marking both for Subject (Agent) and Object (Patient), whereas MSH has differentiated these case markers, 2) Old Hindi has two types of agreement - (a) only with unmarked S/O and (b) both with unmarked and marked S/O, while MSH allows only the first one.